Factores familiares y conocimientos sobre VIH/SIDA en estudiantes de secundaria de una Institución Educativa Estatal de Trujillo - Gamboa Dominguez, Luis Eli (2005)
The present work of investigation is of descriptive type correlacional of transverse court(cut), the study was realized in teenagers of the Educational Institution N º 80010 "Ricardo Palma". Trujillo during December, 2006, with the purpose of determining the relation that exists between the type of family, the size of the family, family revenue and the family functionality and the level of knowledge on VIH. The sample was constituted by 111 students of secondary who expired with the criteria of incorporation. The information was obtained across a constructed survey and the Apgar Familiar; valid and reliable, who was applied considering the rights of anonymity, free participation and confidentiality. The results were analyzed statistically the proof being applied of chi square, being that the type of family, the size of the family, family revenue and the family functionality are not related significantly to the knowledge on VIH/SIDA.